Optimalisasi Produksi Budidaya Ikan Nilai Melalui Ekonomi Sirkular di Pokdakan Dukuh Gangga - Nyoman Yudiarini; Ni Putu Anglila Amaral; I Putu Chandra Ari Wiguna (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2024)
Fish production is getting better from year to year. However, in order to meet the needs of the domestic and inter-regional markets, the amount of production must continue to be increased. Because the potential it has is very possible to make this happen. This research aims to find out how the income of tilapia cultivation compares before and after implementing the circular economy development program in Pokdakan, Dukuh Gangga Sedana, Bunutin Village, Bangli Regency and to find out what obstacles are faced in efforts to optimize circular economy-based tilapia production in Pokdakan. Dukuh Gangga Sedana, Bunutin Village, Bangli Regency. This research involved 10 respondents as research subjects to collect relevant data and support analysis in achieving objectives. This research uses quantitative methods using cost and income data analysis, business feasibility. The results of this research show that before the program, the anorganic method generated a net income of IDR. 18,148,542 and after the program, the organic method reduced production costs and increased income to Rp. 27,132,342, the percentage difference is approx 49,5%.